PARTISIPASI MASYARAKAT LOKAL DALAM KEGIATAN KEPARIWISATAAN DI DESA JATILUWIH KABUPATEN TABANAN - Ni Putu Yessy Apriana Safitri; I Made Sukana (JURNAL DESTINASI PARIWISATA, 2013)
ABSTRACT This research is about local community’s participation of tourism activities in Jatiluwih village Tabanan regency. Jatiluwih has not been considered to give a positif impact to local community. Therefore, Community Based Tourism (CBT) is needed to increase community’s participation. The importance of this study to determine the form of community’s participation in tourism activities Jatiluwih village and to determine the level of community participation of tourism activities in Jatiluwih village. The results of the study shows that participation of local communities is the implementation of Community-Based Tourism (CBT). Community’s participation of Jatiluwih Village in the form of direct participation and indirect participation, where the direct participation of local communities in Jatiluwih Village is a conscious community’s participation that is directed to develop tourism as a homestay provider, provider of restaurants and food stalls, admission officers, a local tour guide and security guard while indirect participation is participation does not directly receive contributions from travelers such as farmers, janitors, cooperative management of tourism and Karang Taruna management. Further participation in the Jatiluwih Village measured by four indicators to determine the level of participation of local communities in tourism in the Jatiluwih Village.